Reinstatement of Cirsium belingschanicum (Asteraceae, Cardueae) as distinct from C. japonicum - Jin, Zi-Chao; Chen, You-Sheng (Phytotaxa, 2025)
Cirsium belingschanicum (Asteraceae), a species from southwestern China, has been previously reduced to the synonymy of C. japonicum. Upon observations of herbarium specimens and living plants in the field, we determine that C. belingschanicum is a distinctive species and thus reinstate its independent specific status herein.